The psychological impacts of travel on students: benefits of study abroad - Meyer, Claire R., author; Garvey, Sara, advisor; Zwick-Tapley, Sarah, committee member (Colorado State University. Libraries, 2026)
Study abroad has become an increasingly common piece of US undergraduate education. This writing serves to investigate the current literature on study abroad and its impacts on students' mental health, identity development, and intercultural outcomes through learning and living in international locations. Prior research showcases that international travel fosters an environment for growth and stress during the experience. This allows study abroad a unique opportunity to examine students' wellbeing and developmental changes over this period. This project analyzes current literature on the psychological impacts of study abroad with a focus on mental health outcomes, identity development, and intercultural learning. Reviewing and synthesizing peer-reviewed empirical studies from the past decade with related findings to this focus. Experiential Learning Theory, Intercultural Development Theory, and Stress and Coping Theory are then drawn upon to back up research findings showcasing the links to gains in resilience, coping skills, cultural humility, empathy, and global awareness, along with shifts in self and American identity. The literature also documents common significant stressors such as pre-departure anxiety, cultural adjustment challenges, and difficulty with re-entry, and how they help to shape the overall psychological development trajectory of study abroad students. Although this covers various insights, current research is limited by small sample sizes, short program durations, and a lack of longitudinal and demographically diverse studies. Understanding these patterns is key to highlight for researchers and practitioners. These works underline the transformative potential of study abroad experiences, while these unstudied topics highlight a need for international programs designed to support well-being and be more purposeful about addressing research on developmental and intercultural impact.
Keywords: study abroad; international travel; mental health; psychological growth; learning; intercultural development; resilience; self-identity; cultural humility